Sex differences in cognitive domains and their clinical correlates in higher-functioning autism spectrum disorders - Bölte, Sven; Duketis, E.; Poustka, F.; Holtmann, M. (2011)
Despite the skewed sex ratio, few studies have addressed possible cognitive sex differences in autism spectrum disorders (ASDs). This study compared visual attention to detail (ATTD) and selected executive functions (EF) in 35 males and 21 females with higher-functioning ASD and unaffected sibling controls. Females with ASD outperformed males on EF as assessed by the Trail Making Test B-A. Males with ASD showed superior performance for ATTD as measured by the Block Design Test (BD) when compared with females. EF difficulties in males were correlated with more stereotypic behaviours and interests on the Autism Diagnostic Interview-Revised or the Autism Diagnostic Observation Schedule. The results indicated clinically meaningful cognitive sex differences in ASD, particularly an association between EF and stereotypic behaviours and interests. ATTD as a potential basis for specific cognitive strengths (e.g. scientific/savant skills) might be more pronounced in males with ASD.